The Role of Carbon Doping on Breakdown, Current Collapse, and Dynamic On‐Resistance Recovery in AlGaN/GaN High Electron Mobility Transistors on Semi‐Insulating SiC Substrates. Issue 7 (10th December 2019) - Zagni, Nicolò; Chini, Alessandro; Puglisi, Francesco Maria; Pavan, Paolo; Verzellesi, Giovanni
Abstract : Herein, the critical role of carbon doping in the electrical behavior of AlGaN/GaN high electron mobility transistors (HEMTs) on semi‐insulating SiC substrates is assessed by investigating the off‐state three‐terminal breakdown, current collapse, and dynamic on‐resistance recovery at high drain–source voltages. Extensive device simulations of typical GaN HEMT structures are conducted and compared with experimental data from published, state‐of‐the‐art technologies to 1) explain the slope of the breakdown voltage as a function of the gate‐to‐drain spacing lower than GaN critical electric field as a result of the nonuniform electrical field distribution in the gate–drain access region; 2) attribute the drain current collapse to trapping in deep acceptor states in the buffer associated with carbon doping; and 3) interpret the partial dynamic on‐resistance recovery after off‐state stress at high drain–source voltages as a consequence of hole generation and trapping. Abstract : Herein, a carbon‐related buffer‐trap model for AlGaN/GaN high electron mobility transistors (HEMTs) is developed by calibrating device simulations on static current–voltage characteristics and breakdown measurements. With this model, it is possible to explain the experimentally observed dynamic on‐resistance recovery after off‐state stress with hole generation and trapping in carbon‐related deep acceptor states in the buffer.